2021
DOI: 10.1371/journal.pone.0257206
|View full text |Cite
|
Sign up to set email alerts
|

Dabrafenib, idelalisib and nintedanib act as significant allosteric modulator for dengue NS3 protease

Abstract: Dengue virus (DENV) encodes a unique protease (NS3/NS2B) essential for its maturation and infectivity and, it has become a key target for anti-viral drug design to treat dengue and other flavivirus related infections. Present investigation established that some of the drug molecules currently used mainly in cancer treatment are susceptible to bind non-active site (allosteric site/ cavity) of the NS3 protease enzyme of dengue virus. Computational screening and molecular docking analysis found that dabrafenib, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In addition, an analysis of Figure 3 In addition, an analysis of Figure 3 showed that the RMSD values of the NS2B/NS3pro-ZINC000001679427 and NS2B/NS3pro-ZINC000001680989 complexes fluctuated within a range of ±1.2 Å over time, thus exhibiting the greater stability of the protein complex link during the simulation [22]. Notably, these binders presented the best PLPChem score and interacted with the essential residues for inhibition at the DENV NS2B/NS3 allosteric site [12,13,16].…”
Section: Molecular Dynamicsmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, an analysis of Figure 3 In addition, an analysis of Figure 3 showed that the RMSD values of the NS2B/NS3pro-ZINC000001679427 and NS2B/NS3pro-ZINC000001680989 complexes fluctuated within a range of ±1.2 Å over time, thus exhibiting the greater stability of the protein complex link during the simulation [22]. Notably, these binders presented the best PLPChem score and interacted with the essential residues for inhibition at the DENV NS2B/NS3 allosteric site [12,13,16].…”
Section: Molecular Dynamicsmentioning
confidence: 98%
“…Typically, the tails (N-and C-terminals) fluctuate more than any other part of the protein. Secondary structure elements such as alpha helices and beta strands are usually more rigid than the unstructured part of the protein and thus fluctuate less than the loop regions [16]. In the NS2B/NS3pro-ZINC000001680989, NS2B/NS3pro-ZINC000001684485 and NS2B/NS3pro-ZINC000006694490 complexes, the rate of fluctuation is higher at residue No.…”
Section: Molecular Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme is conserved among the established four serotypes of the virus viz, DENV1, DENV2, DENV3, and DENV4 that are primarily responsible for dengue hemorrhagic fever or dengue shock syndrome. 1 There are approximately 100 million annual cases of dengue virus infection seen worldwide with a fatality rate of more than 2.5%. 2 The virus is spread from a dengue patient to healthy individuals via the bite of infected female Aedes mosquitoes (Aedes aegypti and Aedes polynesiensis).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The trypsin-like NS2B/NS3 serine protease of dengue virus (DENV) is a classic example of such natural proteases. The enzyme is conserved among the established four serotypes of the virus viz, DENV1, DENV2, DENV3, and DENV4 that are primarily responsible for dengue hemorrhagic fever or dengue shock syndrome …”
Section: Introductionmentioning
confidence: 99%